Evaluation of cytotoxicity, anti-herpes simplex virus type 1 (HSV-1) and antibacterial activities of Ficus vasta and phytoconstituents (International Current Pharmaceutical Journal, 2013)
This study deals with the evaluation of in vitro cytotoxicity of the methanol 80% extract of Ficus vasta aerial parts in Vero cells, anti-HSV-1 and antibacterial activities and the determination of the phytochemical content of the F. vasta methanol extract. The extract was tested for its cytotoxicity in Vero cells and for anti-HSV-1 and against bacterial strains as S. aureus, S. epidermidis, E. coli and P. aeruginosa and also phytochemical constituents were detected. The results showed that this extract presented a CC50 value of 389 µg/mL, an intermediate value taking into account other researchers reported for some Moraceae species. Regarding the other biological activities, antiviral effect was not demonstrated by a HSV-1 challenge dilution of 100x tissue culture infective dose 50% (TCID50) and also by the disk-diffusion method at the higher non-toxic concentration of the extract (119 µg/mL). Phytochemical analysis of the methanol extract proved the presence of carbohydrates, tannins, flavonoids, coumarins, alkaloids and triterpenes. Chromatographic separation of the methanol extract resulted in the isolation and identification of ?-sitosterol, stigmasterol, lupeol, ursolic acid, naringenin, luteolin, quercetin, vitexin, quercetin 3-O-?-glucoside and rutin. The results indicated that F. vasta aerial parts methanol extract is potential candidate for experiments of biological activity screening that are not anti-HSV-1 or antibacterial against the strains evaluated in this study, to be carried on in the future.DOI: http://dx.doi.org/10.3329/icpj.v3i1.17295 International Current Pharmaceutical Journal, December 2013, 3(1): 211-218